PERAN KOMISI PEMBERANTASAN KORUPSI (KPK) SEBAGAI PENYIDIK DAN PENUNTUT TINDAK PIDANA KORUPSI DALAM PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG (STUDI PUTUSAN NOMOR: 10/PID/TPK/2014/PT.DKI ; NOMOR: 1195 K/PID.Sus/2014 ; NOMOR: 2223 K/PID.SUS/2012) - Frima A Sitanggang; Bismar Nasution; Alvi Syahrin; Mahmud Mulyadi (Universitas Sumatera Utara, 2018)
ABSTRACT KPK (Corruption Eradication Committee) is a state institution which independently prevents and eradicates criminal acts of corruption and money laundering. The research problems are, firstly, how about the role of KPK as the investigator and prosecutor of corruption criminal act to eradicate the money laundering criminal act; secondly, how about the obstacles of the role of KPK as the investigator and prosecutor of the corruption criminal act to eradicate the money laundering criminal act; and thirdly, what about the solutions to overcome the obstacles of the role of KPK as the investigator and prosecutor of corruption criminal act to eradicate the money laundering criminal act. These problems will be analyzed through a study on the Rulings No. 10/PID/TPK/2014/PT.DKI; No. 1195 K/PID.Sus/2014; and No. 2223 K/PID.Sus/2012. Legal System Theory is used as the theoretical framework used for the analysis in this research which covers the Legal Structure, Legal Substance and Legal Culture. The results of the research show that KPK has incorrectly charged on the indictment to the perpetrator. The indictment of KPK to the perpetrator is cumulative and contrary to the Article 65 of KUHP (the Penal Code). The role of KPK to return the state loss and to seize the perpetrator’s wealth resulted from the money laundering has been performed by KPK and the legality of the action of KPK has to be based on the laws without violating the order of the prevailing laws. The obstacles encountered by KPK in the prevention and eradication of the money laundering criminal act are, obstacles from the Perspectives of Laws, Law Enforcer, and Legal Culture. Keywords: Investigator, Prosecutor, Corruption, Money Laundering, KPK